2022
DOI: 10.1101/2022.03.14.483815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human bone marrow organoids for disease modelling, discovery and validation of therapeutic targets in hematological malignancies

Abstract: A lack of models that recapitulate the complexity of human bone marrow has hampered mechanistic studies of normal and malignant hematopoiesis and the validation of novel therapies. Here, we describe a step-wise, directed-differentiation protocol in which organoids are generated from iPSCs committed to mesenchymal, endothelial and hematopoietic lineages. These 3-dimensional structures capture key features of human bone marrow - stroma, lumen-forming sinusoidal vessels and myeloid cells including pro-platelet fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Several recent reports have demonstrated the utility of organ-on-a-chip (Ooc) solutions for the recreation of adult bone marrow environments in physiological (Sugimura et al, 2020; Torisawa et al, 2014) and pathological (Abdullah Obaid Khan et al, 2022; Chou et al, 2020), i.e. leukemia settings.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have demonstrated the utility of organ-on-a-chip (Ooc) solutions for the recreation of adult bone marrow environments in physiological (Sugimura et al, 2020; Torisawa et al, 2014) and pathological (Abdullah Obaid Khan et al, 2022; Chou et al, 2020), i.e. leukemia settings.…”
Section: Discussionmentioning
confidence: 99%
“…In an alternative approach, induced pluripotent stem cells are initially aggregated and induced towards mesodermal aggregates, 90 modifying our initial BVO protocol. 41,42 After induction towards vascular and hematopoietic lineage through addition of BMP4, FGF2, VEGF-A, SCF (stem cell factor), and Flt3 (Fms-like tyrosine kinase 3), the organoids were embedded in a hydrogel of collagen/Matrigel mixture.…”
Section: Organotypic Vasculature and Specific Functionsmentioning
confidence: 99%
“…It was demonstrated that this system allows for drug screening in the context of myelofibrosis, but more importantly supports the engraftment of primary patient cells from several cancers which have been classically difficult to study ex vivo (primary myelofibrosis, multiple myeloma, acute lymphocytic leukemia). 230 …”
Section: Theme 4: Hemostasis In Extracorporeal Systems: the Value And...mentioning
confidence: 99%